2010
DOI: 10.1007/s12630-010-9291-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance for internal jugular vein cannulation: Continuing Professional Development

Abstract: Purpose The objective of this continuing professional development module is to describe the role of ultrasound for central venous catheterization and to specify its benefits and limitations. Although ultrasound techniques are useful for all central venous access sites, the focus of this module is on the internal jugular vein approach. Principal findings In recent years, several studies were published on the benefits of ultrasound use for central venous catheterization. This technique has evolved rapidly due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
14
0
3
Order By: Relevance
“…The right IJV was dominant in only 68% of these cases and 23% of the 160 IJVs had a cross-sectional area of 0.4 cm 2 or less. Thus, Ayoub et al [7] suggested that use of USG for CVC should be adopted by new clinicians and experienced practitioners as their first-line treatment, especially in cases of obesity, edema, coagulation disorders, and difficult anatomical landmarks. In this case, if sufficient attention had been paid to the possibility of secondary changes of vessels caused by The diameter of the IJV is smaller than in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The right IJV was dominant in only 68% of these cases and 23% of the 160 IJVs had a cross-sectional area of 0.4 cm 2 or less. Thus, Ayoub et al [7] suggested that use of USG for CVC should be adopted by new clinicians and experienced practitioners as their first-line treatment, especially in cases of obesity, edema, coagulation disorders, and difficult anatomical landmarks. In this case, if sufficient attention had been paid to the possibility of secondary changes of vessels caused by The diameter of the IJV is smaller than in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the utility of ultrasound has been well established, some problems remain even when ultrasound is used, such as accidental arterial puncture or penetration of the posterior wall of the internal jugular vein. 1,2 To minimize mechanical injury, the use of a micropuncture technique with a fine needle and guidewire has been proposed. 3 It is currently unknown whether the micropuncture technique reduces complications when compared with the larger needle and guidewire method typically used for internal jugular vein cannulation.…”
Section: To the Editormentioning
confidence: 99%
“…4 Before dilation, it is essential to confirm the guidewire within the venous lumen to avoid severe mechanical injury that may result from dilation. 1 Nevertheless, a standard relatively large guidewire is sometimes invisible on the ultrasound image, 4 and a thin guidewire can be even more difficult to visualize. To overcome this problem, we push the neck skin softly with the index finger just caudal to where the wire penetrates the skin after removal of the needle (Fig.…”
Section: To the Editormentioning
confidence: 99%
“…En la vena subclavia los resultados aún son dispares probablemente por razones anatómicas. En centros que cuentan con ultrasonido, debe ser usado en forma rutinaria en todos los pacientes [12][13][14][15][16][17] .…”
Section: Figura 5 Ubicaciones Anatómicas Más Frecuentes De La Vena Yunclassified